The Political Relevance of Privacy: An Emotional Approach (Chile, 1800-1840) - Sadarangani, Javier (Privacy Studies Journal, 2025)
This article explores the political relevance of privacy in Chile during the early nineteenth century, focusing on the relationship between public and private spheres through the role of emotions in politics. It argues that privacy became another field of political action, shaped by both political institutions and individual agencies in order to meet the demands of the emerging republican project. Political leaders such as Bernardo O’Higgins and Diego Portales exemplify the emotional self-education required to align private virtues with public ideals that were in line with the institutional legislation. While O’Higgins embraced institutional imperatives, Portales resisted them, marking a shift towards individuality and the gradual emergence of a public–private divide in Chile. To this end, sources such as newspapers, parliamentary debates, dictionaries, philosophical treatises and, above all, letters are analysed within the frameworks of both the history of emotions and egodocuments.